2016
DOI: 10.1590/1983-1447.2016.esp.2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Escolares hospitalizados: proposta de um instrumento para coleta de dados à luz da teoria de Horta

Abstract: The instrument has contributed to data collection in teaching hospitals and has guided the other phases of the nursing process, considering the specific needs of these children, collaborating with the nursing care, education and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
0
5
0
7
Order By: Relevance
“…However, it can be observed that the approach to the theme in the health literature has not considered the children specificities and their development process, which can lead to a reduced health care to their real needs. What can be seen is the use of concepts that were elaborated for the adult population, as is the case of the basic human needs by Wanda Horta (8)(9) , in Brazil, or by Maslow, in international studies (10)(11) .…”
Section: Introductionmentioning
confidence: 99%
“…However, it can be observed that the approach to the theme in the health literature has not considered the children specificities and their development process, which can lead to a reduced health care to their real needs. What can be seen is the use of concepts that were elaborated for the adult population, as is the case of the basic human needs by Wanda Horta (8)(9) , in Brazil, or by Maslow, in international studies (10)(11) .…”
Section: Introductionmentioning
confidence: 99%
“…La síntesis elaborada a partir de los artículos seleccionados muestra que la motivación para la validación de instrumentos para el cuidado en pediatría es diversa y está ligada a hechos como: acceso intravenoso, dermatitis atópica, pacientes pediátricos con cáncer, calidad de vida de niños con parálisis cerebral, preoperatorio en pediatría, patrón del sueño, diagnósticos de autismo, riesgo para la lesión de la piel en los niños y el neonato, recolección de datos en adolescentes, competencias para la alimentación oral, dolor en adolescentes, clasificación de cuidados pediátricos; en los estados de São Paulo y Paraíba, Brasil, autores en sus estudios crearon y validaron instrumentos utilizados para el levantamiento de datos de los pacientes internados en el sector pediátrico, así como para el análisis de características pertinentes a tratamientos y condiciones diagnósticas (13,16) . Además de ser utilizados en la asistencia para la conducción del cuidado y formulación diagnóstica del enfermero para con su equipo, los instrumentos trabajados en pediatría son objetivos de las investigaciones de validación desarrolladas a partir de la búsqueda volcada a la gran área de salud del niño con foco en el niño hospitalizado (14)(15)(16) .…”
Section: Discussionunclassified
“…Validación de la Apariencia, se destina a la validación del instrumento utilizado con fines de evaluación de la adecuación de los ítems, su relación con los componentes estructurales del instrumento y, también, con todo el contenido presente en las entrelíneas. Es un tipo de validación subjetiva y no muy sofisticada, pero bastante utilizada en estudios de fondo metodológico (16,28) .…”
Section: Discussionunclassified
“…Thus, nurses find in the Nursing Process (NP) the methodological path that makes it possible to identify, monitor, understand, describe and explain the needs of a person, the family or even the human community as it guides, directs and organizes professional care. To provide scientific support, it is anchored in a theoretical model and, in Brazil, the most used has been the Theory of Basic Human Needs (TBHN), by Horta, which guides nursing care at the psychobiological, psychosocial and psycho-spiritual levels (6) .…”
Section: Introductionmentioning
confidence: 99%